FACTORS AFFECTING THE ADOPTION OF STRATEGIC MANAGEMENT ACCOUNTING TECHNIQUES IN PUBLIC UNIVERSITIES: ANALYTICAL THEORETICAL RESEARCH - Majid Humeedi Khalaf; Prof. Dr. Ali Ibrahim Hussein (Scholar Express Journals, 2023)
The research aimed to identify the factors affecting the adoption of applying strategic management accounting techniques in public universities. The research dealt with the basic concepts of some of the techniques that were applied in public universities. Relied on the descriptive analytical approach to describe the phenomenon under research according to a theoretical framework supported by a group of Arab and foreign researches that dealt with the adoption of strategic management accounting techniques in public universities. The research concluded that there are many external and internal factors that affect the application of strategic management accounting techniques in public universities. As for the external ones, the most prominent of them is the political factors, since public universities are affiliated with the government and their management is not financially and administratively independent, and therefore they are bound by government provisions and legislation. As well as other factors. Influencing within the universities themselves, from the reluctance of the workers and employees therein to apply the technologies to the lack of knowledge of these technologies and the benefits that result from their application
Keywords: Strategic management; accounting techniques; public universities